Bridging the Gap: Exploring the Relationship between Information Access and Environmental Justice in Library Practices - Oluwole Durodolu; Bolaji Oladokun (Folia Toruniensia)
Aims: The intersection of information access and environmental justice has become increasingly vital as communities worldwide grapple with environmental challenges. This study explores the relationship between information access and environmental justice in library practices, focusing on academic librarians at the Federal University of Technology Ikot Abasi in Nigeria’s Niger Delta region.